Climate change and the demand for recreational ecosystem services on public lands in the continental United States. (September 2021) - Wilkins, Emily J.; Chikamoto, Yoshimitsu; Miller, Anna B.; Smith, Jordan W.
Highlights: Shifting seasonality of demand for recreational ES in parks as temperatures warm. Projected increase in demand for recreational ES in the winter under climate change. Projected decrease in demand for recreational ES in the summer under climate change. Changes in the demand under climate change vary by region and season. Abstract: Cultural ecosystem services represent nonmaterial benefits people derive from the environment; these benefits include outdoor recreation opportunities. Changes in climatic conditions are likely to shift the spatial and temporal demand for recreational ecosystem services. To date, little is known about the magnitude and spatial variability in these shifts across large geographic extents. We use 14 years of geotagged social media data to explore how the climatological mean of maximum temperature affects the demand for recreational ecosystem services by season across public lands in the continental United States. We also investigate how the demand for recreational ecosystem services on public lands may change by 2050 under two climate change scenarios, RCP 4.5 and RCP 8.5. Across all public lands in the continental U.S., demand for recreational ecosystem services is expected to decrease 18% by 2050 under RCP 4.5 in the summer, but increase 12% in the winter and 5% in the spring, with no significant changes in the fall. There is substantial variation in the magnitude of projected changes by region. In the spring and fall, some regions are likely to see an increase in the demand for recreational ecosystem services (e.g., Arkansas-Rio Grande-Texas-Gulf), while others will see declines (e.g., South Atlantic Gulf, California Great Basin). Our findings suggest the total demand for recreational ecosystem services across the continental U.S. is expected to decline under warming temperatures. However, there is a large amount of variation in where, when, and by how much, demand will change. The peak season for visiting public lands is likely to lengthen in the continental U.S. as the climate continues to warm, with demand declining in the summer and growing in the off-season.